Reframing first-generation entry: how the familial habitus shapes aspirations for higher education among prospective first-generation students. Issue 3 (16th April 2021) - Patfield, Sally; Gore, Jenny; Fray, Leanne
ABSTRACT: Despite the shift from elite to mass education, the odds of accessing university remain stacked in favour of those with a university-educated parent. Not only are first-generation students less likely to engage in higher education, but the dominant narrative surrounding their enrolment emphasises cultural deficiency, constructing individuals as 'too different' to succeed. Drawing on data from focus groups with 198 school-aged students in Australia, this paper reframes this narrative by using the concept of familial habitus to examine how aspirations for higher education are shaped and nurtured by the home lives of prospective first-generation entrants. We develop three characterisations of familial habitus – 'projected', 'meritocratic', and 'supportive' – each of which demonstrates the inventive and transformative power of habitus. Cautioning against pathologising accounts of first-generation entry, we argue that the social justice motives of widening participation will be thwarted unless first-generation students are repositioned as legitimate participants in higher education.